Pleuroparenchymal fibroelastosis diagnosed by multidisciplinary discussions in Japan. (August 2018) - Ishii, Hiroshi; Watanabe, Kentaro; Kushima, Hisako; Baba, Tomohisa; Watanabe, Satoshi; Yamada, Yoshihito; Arai, Toru; Tsushima, Kenji; Kondoh, Yasuhiro; Nakamura, Yutaro; Terasaki, Yasuhiro; Hebisawa, Akira; et al.
Abstract: Background: Pleuroparenchymal fibroelastosis (PPFE) is a rare subset of idiopathic interstitial pneumonias. No large-scale clinical studies of PPFE have been published. The aim of the study was to clarify the clinical and physiological characteristics of PPFE in Japan Methods: This was a retrospective, nationwide, and multicenter study in Japan. We reviewed 52 patients with PPFE, diagnosed after multidisciplinary discussions. Results: Flat chest index, defined as the ratio of anteroposterior diameter to transverse diameter of thoracic cage at the level of 6th thoracic vertebra, correlated positively with body mass index (BMI) ( r  = 0.340, p  = 0.013) and percentage of predicted value of forced vital capacity (FVC %pred) ( r  = 0.355, p  = 0.012), and negatively with the ratio of residual volume to total lung capacity (RV/TLC) ( r  = −0.312, p  = 0.042). RV/TLC correlated negatively with BMI ( r  = −0.746, p  < 0.0001) and FVC %pred ( r  = −0.507, p  = 0.0005), and positively with age, and physiological variables (GAP) scores ( r  = 0.332, p  = 0.030). The median survival time and the cumulative 5-year survival rate were 96 months and 58%, respectively. Patients with KL-6 level >600 (U/mL) survived shorter than those with <600 ( p  < 0.001). Conclusion: Low BMI, decreased FVC and increased RV/TLC in PPFE may be related to the progression of flattened chest cage which impairs distension of chest cage at inspiration. Elevated serum levels of KL-6 suggest a poor prognosis of PPFE. Highlights: This is the largest case series for PPFE diagnosed after multidisciplinary discussions. Low-compliant thoracic cage, flat chest, modifies the pathophysiology of PPFE. Remarkably decreased FVC and increased RV/TLC are functional characteristics in PPFE. Elevated levels of serum KL-6 suggest a poor prognosis of PPFE.